Intravenous cyclophosphamide treatment for systemic lupus erythematosus with severe autonomic disorders confirmed by head-up tilt table test: A case series. Issue 1 (2nd October 2021) - Umeda, Masataka; Kawano, Hiroaki; Endo, Yushiro; Takatani, Ayuko; Koga, Tomohiro; Ichinose, Kunihiro; Nakamura, Hideki; Mukaino, Akihiro; Higuchi, Osamu; Nakane, Shunya; Maeda, Takahiro; Kawakami, Atsushi
ABSTRACT: Autonomic disorders are common in patients with systemic lupus erythematosus (SLE), but the therapeutic strategy and methods for evaluating the effects of therapy have not been established. We describe the three cases of SLE patients who developed severe autonomic disorders as demonstrated by the head-up tilt table test (HUT). All three patients were treated by intensive immunosuppressive treatments including intravenous cyclophosphamide (IVCY); their HUT results all became negative. Our cases suggest that IVCY treatment can be a good therapeutic option for severe autonomic disorders in SLE patients. The HUT is a useful objective method for the diagnosis of and the evaluation of longitudinal therapeutic effects on autonomic disorders in SLE patients with orthostatic intolerance.